2009
DOI: 10.1089/ars.2009.2439
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Angiogenesis in Diabetes and Hypercholesterolemia: Influence of Oxidative Stress

Abstract: Despite significant improvements in the medical, percutaneous, and surgical management, numerous patients are first seen with non-revascularizable coronary artery disease (CAD). The growth of new blood vessels to improve myocardial perfusion (i.e., therapeutic angiogenesis) is an attractive treatment option for these patients. However, the successes of angiogenic therapy, observed in preclinical studies, have not been realized in clinical trials. Increasing evidence suggests that this discrepancy between anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 127 publications
0
36
0
Order By: Relevance
“…4,5 Similarly patients with metabolic syndrome have diminished angiogenic responses to chronic ischemia and alterations in a variety of mechanisms contributing to vascular bed dysfunction including the formation of collateral vessels. 6,7 We and other laboratories have reported that a major mechanism leading to vascular dysfunction in metabolic syndrome is increased oxidative stress leading to over production of reactive oxygen species (ROS) and cellular apoptosis. 7,8,9 [Figure 1]…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Similarly patients with metabolic syndrome have diminished angiogenic responses to chronic ischemia and alterations in a variety of mechanisms contributing to vascular bed dysfunction including the formation of collateral vessels. 6,7 We and other laboratories have reported that a major mechanism leading to vascular dysfunction in metabolic syndrome is increased oxidative stress leading to over production of reactive oxygen species (ROS) and cellular apoptosis. 7,8,9 [Figure 1]…”
Section: Introductionmentioning
confidence: 99%
“…VEGF binds and phosphorylates its receptors, leading to the activation of a variety of signaling cascades such as MAPK and Akt. Angiogenic gene therapy using plasmids encoding VEGF has been attempted in patients with coronary or peripheral artery diseases [9]. However, diabetes mellitus people often show a poor response to therapeutic angiogenesis [10].…”
Section: Introductionmentioning
confidence: 99%
“…In the diabetic patient, angiogenesis was found to be associated with retinopathy [45]. In hypercholesterolemia, there was apparent decrease of myocardial vascular density and an increase of endothelial damage [46] which result from ischemia and increase of oxidative stress [47] and reduction in the expression of tissue endothelial nitric oxide synthase [48] (Fig.3).…”
Section: Hypercholesterolemia and Ocular Diseasementioning
confidence: 96%